BASI74, a Virulence-Related sRNA in Brucella abortus - Dong, Hao; Peng, Xiaowei; Liu, Yufu; Wu, Tonglei; Wang, Xiaolei; De, Yanyan; Han, Tao; Yuan, Lin; Ding, Jiabo; Wang, Chuanbin; Wu, Qingmin (Frontiers in Microbiology, 2018)
Brucella spp. are intracellular pathogens that infect a wide variety of mammals including humans, posing great threat to the development of livestock husbandry and human health in developing countries. A number of genes associated with the intracellular trafficking and multiplication have so far been identified in Brucella spp. However, the sophisticated post-transcriptional regulation and coordination of gene expression that enable Brucella spp to adapt to changes in their environment and evade host cell defenses as well as survive in a hostile host environment, have remained poorly understood. Bacteria small RNAs (sRNAs) play significant role in post-transcriptional regulation, which has already been confirmed in a number of bacteria, however, the role of sRNAs in Brucella has remained elusive. In this study, we have identified several different sRNAs in Brucella spp, and found that over-expression of a sRNA, tentatively termed BASI74, led to alternation in virulence of Brucella in macrophage infection model. We demonstrated that the expression level of BASI74 was increased while growing in acidic media. In addition, BASI74 affected the growth ratio of the Brucella cells in minimal media and iron limiting medium. Using a two-plasmid report system, we identified four genes targeting BASI74. Although the functions of three target genes above are unclear, the forth target gene, BABI1154, was determined to encode a cytosine-N4-specific DNA-methyltransferase, which protects cellular DNA from the restriction endonuclease in Brucella. These results show that BASI74 plays an important role in Brucella survival ability in macrophage infection model, which is likely achieved by its connection with stress response or impact on restriction-modification system. Our study provides a basis for better understanding of Brucella sRNAs, as well as the mechanism by which sRNAs use to influence Brucella physiology and pathogenesis.